(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2024)
The Rhomaleosauridae were a clade of Jurassic plesiosaurians, characterized by triangular skulls, elongated preorbital region, marked premaxillary-maxillary constriction, and intermediate body proportions between pliosauromorphs and plesiosauromorphs. Despite recent progress in the study of dental replacement in plesiosaurians, the replacement features in rhomaleosaurids have not been studied. Here, the dental features of the rhomaleosaurid Maresaurus coccai are described and analyzed based on the holotype specimen. Regarding symmetry, it was determined that M. coccai shows symmetrical replacement in the maxillary-premaxillary and asymmetrical replacement in the dentary. Additionally, the tooth replacement cycle period (TRCP) of two alveoli was determined for the dental series, with the exception of the anterior part of the left mandibular ramus, which presents an TRCP of three, an asymmetry considered here as teratology. This result indicates that the replacement cycle period (TRCP) of the two alveoli would correspond to a primitive character for Plesiosauria, observing an increase of TRCP from two to three alveoli in taxa comparatively more derived within Pliosauridae.